School and Industrial Kitchen Sanitation and Hygiene Practices among HRM Graduates - Candilas, Kurt S.; Danuco, Verla Nena T. (Future Science / FSH-PH Publications, 2022)
Kitchen practices such as sanitation and hygiene are crucial precautionary methods in preventing untoward accidents due to carelessness in the kitchen. This study aimed to determine the Hotel and Restaurant Management (HRM) graduates’ kitchen sanitation and hygiene practices in school to their practices in the industry. There were sixty-seven HRM graduates of the College in Cagayan de Oro City employed in the different hotels, restaurants, and chains who participated as the participants of the study. A snowball sampling technique was used. Both descriptive and inferential statistics were used to generate the findings. Generally, results show that school kitchen practices have a minimal implication on HRM graduates’ real-life practices in the industry. Among the kitchen practices, only storage is significantly having an impact on HRM graduates’ practices in both school and industry. Thus, the findings of the study call for the need to intensify school kitchen teaching practices in actualizing real concepts and practices of the kitchen industry.